2021
DOI: 10.3390/agriculture11111105
|View full text |Cite
|
Sign up to set email alerts
|

Mango Fruit Processing: Options for Small-Scale Processors in Developing Countries

Abstract: Postharvest losses of mango fruit in a number of developing countries in Africa and Asia have been estimated to be as high as over 50%, especially during the main harvest season. Micro, small, and medium scale food processing enterprises play an important economic role in developing economies in processing of a diversity of healthy food products as a sustainable way to reduce postharvest losses and food waste, extend shelf life of food, boost food security, and contribute to national gross domestic product. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…Immediately after the PEF, the electrical conductivity of the samples was measured using a conductometer (TDS&EC meter, Zhejiang, China). The electrical conductivity disintegration index (Z) evaluated the degree of tissue damage (Z) [33], as presented in Equation (7).…”
Section: Electrical Conductivity Disintegration Index (Z)mentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after the PEF, the electrical conductivity of the samples was measured using a conductometer (TDS&EC meter, Zhejiang, China). The electrical conductivity disintegration index (Z) evaluated the degree of tissue damage (Z) [33], as presented in Equation (7).…”
Section: Electrical Conductivity Disintegration Index (Z)mentioning
confidence: 99%
“…However, these methods use more pieces of equipment and technology, which might not be suitable for farmers. There are several types of preserved mango products such as canned slices in syrup, juice, nectar, jam, chutney, and dehydrated mango [7]. However, these preserving processes are conducted at the ripening stage.…”
Section: Introductionmentioning
confidence: 99%
“…Maize stored in woven polypropylene bags recorded losses due to insect pests with chemical protectant (northern 4.02 ± 1.23%) versus without (northern 9.64 ± 2.73%). Financial analysis indicated that the most profitable storage technologies were hermetic bags without an initial chemical treatment in central Benin, a more humid region, and woven polypropylene bag with an initial chemical protectant treatment in northern Benin, a more arid region [10]; (11) Review of mango fruit processing options for small-scale processors in lowincome countries. Processing mango fruit into a number of shelf-stable food products makes the seasonal fruit more broadly available to consumers yearround.…”
Section: B Post-harvest Handling and Dryingmentioning
confidence: 99%
“…Byproducts of mango processing, such as peel and kernels, are rich in bioactive compounds including carotenoids, polyphenols, and dietary fibers, can be used in food fortification and manufacture of animal feeds. This adds value to the fruit while reducing food loss and waste [11]-Consortium.…”
Section: B Post-harvest Handling and Dryingmentioning
confidence: 99%
“…Mango is the main tropical fruit with the highest volume of production [ 2 ], also being one of the five most demanded fruits worldwide [ 3 ]. During the industrial processing of mango, peel and stones, the main wastes generated, represent about 35–50% of the fresh fruit [ 4 ]. This solid waste is becoming a source of pollution, because of the high volumes produced, and it is a rising concern when landfilled due to its high biodegradability, organic content, and possible environmental impacts [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%